Atmospheric air pollution from the Ermakovskoe fluorite-beryllium deposit development waste - Alexey M. Plyusnin; Elena R. Garipova; Alexander V. Ukraintsev; Mikhail K. Chernyavskii; Dashima I. Zhambalova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2024)
Relevance. Negative impact of waste from mining enterprises on the ecological state of the surrounding areas. Aim. To determine the migration ability of toxic chemical elements from waste storage sites of the Ermakovskoe beryllium deposit in the air. Object. Ermakovskoe fluorite-bertrandite-phenacite deposit and the surrounding area. Methods. Inductively coupled plasma mass spectrometry, laser diffraction, inductively coupled plasma atomic emission spectrometry. Results and conclusions. The paper introduces the experimental studies of surface atmospheric pollution by mining waste from the Ermakovskoe fluorite-bertrandite-phenakite deposit are presented using an installation for collecting aerosols above the sand surface. It was established that toxic components formed during the decomposition of residual sulfide mineralization and products of the interaction of acidic waters with rocks move from the sand thickness to the surface along with water vapor. The moisture condensed over the sand contains high contents of aluminum, iron, manganese, zinc, and phosphorus. These elements form a halo of air pollution over mining waste and are then dispersed by air currents into the surrounding area. In winter, due to wind dispersion of aerosols, the snow cover becomes contaminated over a vast area. Among the toxic elements found were beryllium, lead, cadmium, and molybdenum, which belong to the second hazard class. The solid residue of the snow cover contains a fine fraction of dust, the size of which is less than 10 microns. The halo of snow contamination with toxic chemical elements and dust extends several kilometers away from the disturbed lands.